Calcium-sensing receptor and aquaporin 2 interplay in hypercalciuria-associated renal concentrating defect in humans. An in vivo and in vitro study. - Giuseppe Procino; Lisa Mastrofrancesco; Grazia Tamma; Domenica Rita Lasorsa; Marianna Ranieri; Gilda Stringini; Francesco Emma; Maria Svelto; Giovanna Valenti (PLoS ONE)
One mechanism proposed for reducing the risk of calcium renal stones is activation of the calcium-sensing receptor (CaR) on the apical membranes of collecting duct principal cells by high luminal calcium. This would reduce the abundance of aquaporin-2 (AQP2) and in turn the rate of water reabsorption. While evidence in cells and in hypercalciuric animal models supports this hypothesis, the relevance of the interplay between the CaR and AQP2 in humans is not clear. This paper reports for the first time a detailed correlation between urinary AQP2 excretion under acute vasopressin action (DDAVP treatment) in hypercalciuric subjects and in parallel analyzes AQP2-CaR crosstalk in a mouse collecting duct cell line (MCD4) expressing endogenous and functional CaR. In normocalciurics, DDAVP administration resulted in a significant increase in AQP2 excretion paralleled by an increase in urinary osmolality indicating a physiological response to DDAVP. In contrast, in hypercalciurics, baseline AQP2 excretion was high and did not significantly increase after DDAVP. Moreover DDAVP treatment was accompanied by a less pronounced increase in urinary osmolality. These data indicate reduced urinary concentrating ability in response to vasopressin in hypercalciurics. Consistent with these results, biotinylation experiments in MCD4 cells revealed that membrane AQP2 expression in unstimulated cells exposed to CaR agonists was higher than in control cells and did not increase significantly in response to short term exposure to forskolin (FK). Interestingly, we found that CaR activation by specific agonists reduced the increase in cAMP and prevented any reduction in Rho activity in response to FK, two crucial pathways for AQP2 translocation. These data support the hypothesis that CaR-AQP2 interplay represents an internal renal defense to mitigate the effects of hypercalciuria on the risk of calcium precipitation during antidiuresis. This mechanism and possibly reduced medulla tonicity may explain the lower concentrating ability observed in hypercalciuric patients.